Experimental Study on Mechanical Properties of Fly Ash Stabilized with Cement - Shengquan Zhou; Yongfei Zhang; Dawei Zhou; Weijian Wang; Dongwei Li; Zhaibang Ke (Advances in Civil Engineering)
Cement-fly ash mixture has been commonly used for the foundation treatment projects in the fly ash stratum, as it is effective in improving foundation bearing capacity and reducing settlement of stratum. In order to figure out the effect of dynamic and static load on the mechanical properties exhibited by the cement-fly ash and the reaction mechanism of cement-fly ash, a combination of the unconfined compressive test, impact test, scanning electron microscopy (SEM), and X-ray diffraction (XRD) method was adopted in this study to investigate the cement-fly ash test samples. As demonstrated by the results, the observed growth rate of 0–60 days (d) is higher than that in the later stages and the typical stress-strain curve can be divided into six sections under the unconfined compressive test. At the gas pressure of 0.2 MPa, the cement-fly ash samples exhibited obvious plastic properties in early curing time (0–60 d), and brittle failure was observed in the final stage (90 d). It is obvious that the value of dynamic compressive strength (DCS) is higher than that of unconfined compressive strength (UCS). The analysis of XRD has revealed that the hydration products are primarily derived from the hydration reaction of cement in the early stage and the pozzolanic reaction in the late stage. The pores of cement-fly ash are found to be filled with the hydration products, despite the presence of a mass of pores in the interior.